Efeito da temperatura de bobinamento nas propriedades mecânicas e microestrutura de um aço multiconstituído da classe de 800 MPa de limite de resistência para aplicação em rodas automotivas - Danilo de Castro Denúbila (2015)
The subject of this study was to assess the effects of coil temperature variation in the mechanical properties and microstructure of a steel grade with 800 MPa of tensile strength, in development at Usiminas, for application in automotive wheels. Once the steel chemical composition had already been defined, industrial scale experiments have been performed, keeping all process variables constant, except the coiling temperature, which was set up to vary between 470°C to 680°C. Dilatometric simulations were carried out to identify the microstrutural evolution at different strip cooling, in the Run Out Table of the Hot Rolling Strip Mill. The resulted microstructure, constituted mainly by a very fine ferrite, having pearlite, bainite and MA constituents, as a second phase, have not significantly modified, for the different experimented coiling temperatures. As consequence, low variation on mechanical properties were obtained. The analysis of these results will allow the suitable coiling temperature definition in reaching the desirable mechanical properties and microstructure according to this steel grade.